1980
DOI: 10.1136/bmj.281.6244.836
|View full text |Cite
|
Sign up to set email alerts
|

Relapses in Wegener's granulomatosis: the role of infection.

Abstract: Summary and conclusionsOut of 20 relapses that occurred in patients with Wegener's granulomatosis, nine were provoked by bacterial or viral infection. Seven of these occurred during maintenance treatment in response to infection with common pathogens, and treatment of the infection alone was insufficient to produce remission. Circulating immune complexes were seen only in relapses due to infection and rarely in infections that occurred without relapse. A possible mechanism for infection-provoked relapses is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
2
6

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(80 citation statements)
references
References 9 publications
1
71
2
6
Order By: Relevance
“…Cardiovascular involvement has been identified as a predictor of a relapse [35]. In a small study, infection has been reported to be a risk factor for GPA [39]. In a larger study, however, we could not confirm this [38].…”
Section: Risk Factors For a Relapsecontrasting
confidence: 54%
“…Cardiovascular involvement has been identified as a predictor of a relapse [35]. In a small study, infection has been reported to be a risk factor for GPA [39]. In a larger study, however, we could not confirm this [38].…”
Section: Risk Factors For a Relapsecontrasting
confidence: 54%
“…In addition to the seasonal association with disease (14), infection may predate the initiation of AAV and can induce disease relapses (35,36). This is particularly true of MPO-associated disease; in one study, 11 of 18 patients with severe crescentic glomerulonephritis had a preceding respiratory tract infection (37).…”
Section: Discussionmentioning
confidence: 99%
“…The production of TNF␣, IL-1, and IL-8 by macrophages is significantly up-regulated when they are incubated with ANCA-opsonized apoptotic neutrophils compared with normal IgG-opsonized or nonopsonized apoptotic neutrophils (34,53). TNF␣ levels prior to development of vasculitis have not been studied, but, since many patients have a history of chronic infection before the onset of vasculitis (54) and intercurrent infection often precedes relapse (55), it is likely that synthesis of TNF␣ is increased. If this is the case, it is conceivable that uptake of apoptotic neutrophils by DCs within an environment rich in TNF␣ might encourage development of an autoimmune response toward neutrophil PR3 or MPO.…”
Section: Discussionmentioning
confidence: 99%